2019
DOI: 10.5114/pjr.2019.92287
|View full text |Cite
|
Sign up to set email alerts
|

Painful clicking jaw: a pictorial review of internal derangement of the temporomandibular joint

Abstract: Temporomandibular joint disorders are a common cause of chronic musculoskeletal pain worldwide. Among these, internal disc derangement is the most frequent type of disorder. Internal derangement is defined as an abnormal positional and functional relationship between the disc and articulating surfaces. Common clinical symptoms include pain and clicking.Imaging plays a key role in diagnosing temporomandibular joint disorders. It is important for the radiologist to detect early imaging signs of internal derangem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Such a stop results in a specific sound-clinically audible as a thud. The phenomenon is physiological and results from the specific anatomy of the articular tubercle, which can be caused by the excessive mouth opening during yawning, singing, vomiting, eating or through factors such as generalised joint hypermobility (GJH), Ehler Danlos syndrome, Marfan syndrome or intubation under general anaesthesia [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a stop results in a specific sound-clinically audible as a thud. The phenomenon is physiological and results from the specific anatomy of the articular tubercle, which can be caused by the excessive mouth opening during yawning, singing, vomiting, eating or through factors such as generalised joint hypermobility (GJH), Ehler Danlos syndrome, Marfan syndrome or intubation under general anaesthesia [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Nosouhian et al reported that TMJH occurs much more frequently in women (78.2%) than in men [11]. Moreover, Mehndiratta et al, using magnetic resonance imaging (MRI), noticed that TMJH is connected with an anatomic variant where the articular eminence has a steep and short posterior slope and a longer anterior slope [2].…”
Section: Introductionmentioning
confidence: 99%
“…Daily activities such as eating of hard foods, gasping, yawning in case of patients with hypermobility of the temporomandibular joints are associated with a speci c sound described as thud (6) . Sounds in the joints created during everyday activities performed by patients draw the attention of others, which is usually embarrassing.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon is physiological and results from the speci c anatomy of the articular tubercle. Among the factors that lead to such a speci c anatomy of the articular tubercle we can distinguish the excessive mouth opening during yawning, singing, vomiting, eating, factors such a generalized joint hypermobility (GJH), Ehler Danlos syndrome or Marfan syndrome and intubation under general anesthesia (5,6). The dynamic compression during excursive gliding and incursive movements con rm subluxation (5)(6)(7) Subluxation may also be considered a non-physiological condition if the patient reports chewing muscle disorders as well as TMJ pain and discomfort.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation